A dual-criterion optimization for sulfonated asphalt-assisted aqueous phase exfoliation to prepare graphene suitable for protective coating of aluminium. (12th February 2020) - Yang, Shengkai; Zhuo, Kelei; Zhang, Zezhong; Yang, Jingli; Chen, Yujuan; Wang, Jianji
Abstract: In this work, we aimed to prepare graphene with high concentration ( C G ) or quality (indicated by I D / I G ) by sonication-assisted exfoliation in aqueous sulfonated asphalt (SAS) solution. The highest C G can reach 0.181 mg ml −1, while the smallest I D / I G is only 0.331 in the investigated range. Meanwhile, we observed that C G and I D / I G changed in the opposite trend with the increase of SAS concentration, and reached their extreme values simultaneously. This was attributed to SAS's agglomeration-induced redistribution of total energy absorbed by graphite between exfoliation and crushing. The graphene size was mainly within 100–400 nm and most of layer number was <5. The stabilization of graphene dispersion comes from the electrostatic repulsion between negatively charged SAS groups adsorbed on the graphene sheets. As the protective coating of aluminium, the graphene with relative small (for H2 SO4 solution) or large (for NaCl solution) size, relative high defect content and annealing at proper temperature can improve the anticorrosion performance of graphene.